Democracy and Public Management Reform - Luiz Carlos Bresser-Pereira (Oxford University Press, 2004)
This book is about the new democratic state that is emerging and about the reform that leads in that direction: public management reform. My central concerns will be, first, to understand how the modern state has transformed itself from the absolute state of early capitalism into the social-democratic state of today, and possibly into the social-liberal and republican state of the twenty-first century; second, to discuss the importance of the strong, legitimate, and democratic state in the global system; and third, to propose a model of public management reform—a tool for building this republican state. The book takes an eclectic and ‘reasonable’ approach to the state and to the institutional reforms that are required which proceeds from the assumption that the Western world-political experience has been one of steady progress. Thus, despite the intense conflicts that have accompanied this progress, the best aspects of republicanism, liberalism, democracy, and socialism are in one way or another present in the modern democracies.1 They are present in ‘reasonable’ terms. Unlike Aristotle in antiquity and John Rawls in the twentieth century, to whom ideas and institutions should be primarily reasonable, most political theorists of the past have treated ideologies or political doctrines in pure or radical terms. Such an unreasonable approach makes argumentation inoperative and compromise impossible, even though argumentation and compromise are the two major tools with which democracy achieves quasi-consensus and improves its institutions. The deliberately eclectic and reasonable approach in this book is coupled with a distinctly republican view of politics, since I believe that our political and social system is the outcome of the endeavour of self-interested citizens who are nevertheless able to perceive and promote the public interest. I do not share the dominant view in the social sciences that the social world is regulated by natural laws. I agree that structural constraints have to be taken into consideration, provided that this approach does not lead to moral cynicism or to generalized pessimism. A republican approach is neither cynical nor voluntarist. It assumes that institutional reform is possible, but that this process is the collective and often conflicting outcome of many minds, of all kinds of interests, and of different technical and emotional competencies in formulating and implementing public policies. Reforms will often be second-hand and biased towards the rich, leaving the poor unhappy and protesting. Republicanism has traditionally